Palladium-catalyzed polar solvent empowered synthesis of hyper-branched ethylene oligomers and their applications - Birajdar, Rajkumar S.; Gonnade, Rajesh G.; Pol, Harshawardhan V.; Prabhu, M. Basava; Rokade, Dhammaraj; Nandimath, Sheetal; Chikkali, Samir H. (Polymer Chemistry, 2023)
In this contribution, we report the synthesis of two naphthoxy imine ligands, 2-(((2,6-dibenzhydryl-4-methoxyphenyl)imino)methyl)naphthalen-1-ol (L1) and 2-(((2,6-diisopropylphenyl)imino)methyl)naphthalen-1-ol (L2), with different steric and electronic features. L1 and L2 were treated with [(TMEDA)PdMe2] to obtain the corresponding neutral palladium(ii) complexes Cat.1 and Cat.2 in excellent yields. The identity of Cat.1 and Cat.2 was unambiguously ascertained using a combination of spectroscopic and analytical methods, including single-crystal X-ray diffraction. When exposed to 5 bar ethylene pressure, Cat.1 produced hyperbranched ethylene oligomers. The microstructure analysis of ethylene oligomers confirmed the existence of methyl, ethyl, propyl, and sec-butyl branches, with a molecular weight (M-n) of 500-1400 g mol(-1), a PDI of 1.46-2.10, and 67-106 branches per 1000 carbon atoms. The use of a polar solvent, tetrahydrofuran, led to a remarkable 3-fold increase in oligomerization activity without compromising the branching and molecular weight. The resultant hyperbranched ethylene oligomers were selectively monofunctionalized using industrially practiced hydroformylation, ozonolysis, and epoxidation, almost quantitatively. The hydroxy functionalized ethylene oligomer (F4) (5 wt%) was melt-compounded with LLDPE and Nylon-6 to produce a tough yet flexible blend with a higher strain-to-failure as compared to an uncompatibilized blend.